GEORGIA’S TRADE POLICY AND FREE TRADE AGREEMENT WITH THE EUROPEAN UNION, REALITY AND FUTURE - Tavartkiladze, Amiran (European Scientific Journal, ESJ, 2014)
The track of Georgia’s integration with the West crosses several basic goals. First and foremost, of course, it is membership in NATO and the European Union. Europe supports those countries which are considered as its strategic partners politically. Today, when the EU really sees that less a developed country tries to follow democratic standards and does not give up important principles of the European civilization, as an encouragement, it creates opportunities to sign a free trade agreement with such country. Today, Georgia is considered in such an aspect. Signing of a free trade agreement with any particular country is definitely oriented to some positive result. However, cooperation of this scale with such conglomerate as the European Union can be viewed also as a kind of indirect guarantee of Georgia’s security. It is worth emphasizing that a free trade agreement is one of the components of the association agreement. Presumably, until the end of 2013, the dates when formal negotiations could start on this issue will be agreed upon. It looks like it will be the second half of 2014. The very fact that free trade with Europe may become real is very positive.